2013
DOI: 10.1007/978-94-007-5702-8_10
|View full text |Cite
|
Sign up to set email alerts
|

The Pleasant Life, the Engaged Life, and the Meaningful Life: What About the Balanced Life?

Abstract: Martin Seligman, in his very popular book Authentic Happiness (Seligman 2002), argued that authentic happiness is derived from three major sets of experiences in life, namely experiencing pleasantness regularly (the pleasant life), experiencing a high level of engagement in satisfying activities (the engaged life), and experiencing a sense of connectedness to a greater whole (the meaningful life). In this chapter, we maintain that balance in life contributes significantly to subjective well-being. Balance cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 41 publications
(28 reference statements)
0
2
0
Order By: Relevance
“…Assigning excessive meaning to one’s work could harm attention toward nonwork domains of life, causing an imbalance between personal and professional lives that in turn diminishes well-being. 115 A qualitative study of nurses found that when an imbalance exists between meaningfulness and manageability of work, the clinicians’ coping resources become depleted, resulting in symptoms of burnout. 116 Harms et al 117 theorized that continuous honing by resilient individuals of personal skills and abilities can enhance their competence and self-efficacy while paradoxically undermining well-being.…”
Section: Discussionmentioning
confidence: 99%
“…Assigning excessive meaning to one’s work could harm attention toward nonwork domains of life, causing an imbalance between personal and professional lives that in turn diminishes well-being. 115 A qualitative study of nurses found that when an imbalance exists between meaningfulness and manageability of work, the clinicians’ coping resources become depleted, resulting in symptoms of burnout. 116 Harms et al 117 theorized that continuous honing by resilient individuals of personal skills and abilities can enhance their competence and self-efficacy while paradoxically undermining well-being.…”
Section: Discussionmentioning
confidence: 99%
“…One approach in conceptualising the effect of the urban environment on well-being is to assume that overall life-satisfaction is affected by satisfaction with certain domains in life, such as one's family life or professional life (Sirgy and Wu, 2013). In a similar vein Sirgy and Cornwell (2002) found empirical support for the fact that life satisfaction is influenced by neighbourhood satisfaction and housing satisfaction, which are influenced by evaluations of specific characteristics such as upkeep of houses and yards, noise and crowding, perceived crime and experienced safety.…”
Section: Conceptualising Well-being and Urban Environmentmentioning
confidence: 99%